Analisis Sistem Penyelenggaraan Rekam Medis di Instalasi Rekam Medis RS “X” Tangerang Periode April-Mei 2015 - Nuraini, Novita (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
This study aims to analyze the medical records implementation system (input, process, output, feedback and control) in the "X" Hospital Tangerang period from April to May 2015. This research is a mixed method. The data collected by observation, interview, documentation. Results: The medical record system implementation was not running optimally so this is due to produce output completeness of medical record file is only 55.2%, while the timeliness of the provision of medical record file is only 31%. This relates to the control and the process does not complete the analysis of the file. Suggestion: Hospital activate Control Committee of medical records and set a completeness analysis activities outpatient medical record.